2016
DOI: 10.1186/s12918-016-0308-x
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of a non-irradiated acute myeloid leukemia model

Abstract: BackgroundComputer-aided, interdisciplinary researches for biomedicine have valuable prospects, as digitalization of experimental subjects provide opportunities for saving the economic costs of researches, as well as promoting the acquisition of knowledge. Acute myeloid leukemia (AML) is intensively studied over long periods of time. Till nowaday, most of the studies primarily focus on the leukemic cells rather than how normal hematopoietic cells are affected by the leukemic environment. Accordingly, the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…On the contrary, given the typical pre-conditioned leukemia models utilized in most of previous studies, the physiology of native leukemogenesis is destroyed, i.e. non-leukemic cells in the leukemic host are no longer the “normal” cells because they are heavily damaged by the myeloablative manipulations and thus deviant far from the normal cellularity [ 7 , 9 , 27 30 ]. Gene expressions in those study designs (other than ours) cannot represent in vivo functions; hence if in those cases, Maff / Egr3 regulations on HSC cell cycle could not have been inferred.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the contrary, given the typical pre-conditioned leukemia models utilized in most of previous studies, the physiology of native leukemogenesis is destroyed, i.e. non-leukemic cells in the leukemic host are no longer the “normal” cells because they are heavily damaged by the myeloablative manipulations and thus deviant far from the normal cellularity [ 7 , 9 , 27 30 ]. Gene expressions in those study designs (other than ours) cannot represent in vivo functions; hence if in those cases, Maff / Egr3 regulations on HSC cell cycle could not have been inferred.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, we found that in leukemic BM, the HPC count increased and the rate that HSCs differentiate into HPCs was high at the beginning; meanwhile, the differentiation of HSCs towards HPCs was almost shut off later and the HPC count decreased acutely after day 14 [ 9 ]. Furthermore, significantly increased quiescence of HSCs was observed at the late stage of leukemia [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the next paper, Li et al digitalized a novel animal model for acute myeloid leukemia, which accounted for both leukemic and normal blood cells in the disease [4]. Specifically, the authors modeled multi-tissue hematopoietic dynamics in the leukemic body.…”
Section: Introductionmentioning
confidence: 99%